PENGARUH KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN MELALUI MEDIASI DISIPLIN KERJA (Pada LPK Monarch Candidasa) - I Putu Gede Adi Suparta (Universitas Warmadewa, 2017)
This study aimed at analysing and describing the effects of leadership and motivation toward employee’s performance through mediation of job discipline as a variable. The subject of this study was LPK Monarch candidasa. The hypothesis were ; (1) leadership had a positive and significant effect toward the job discipline of employee at LPK Monarch Candidasa ; (2) motivation had a positive and significant effect toward the job discipline of employee at LPK Monarch Candidasa ; (3) leadership had a positive and significant effect toward the employee’s performance at LPK Monarch Candidasa ; (4) motivation had a positive and significant effect toward the employee’sperformance at LPK Monarch Candidasa ;(5) discipline had a positive and significant effect toward the employee’s performance at LPK Monarch Candidasa. This study used qualitative design with 31 people as the respondens. The data used in this study were primary and secondary data for both qualitative and quantitative data. The data were analyzed using Structural equation modeling (SEM) with partial least square (PLS) method. The results of this study were : (1) leadership had a positive and significant effect toward the job discipline of employee; (2) motivation had a positive and significant effect toward the job discipline of employee; (3) leadership had a positive and significant effect toward the employee’s performance; (4) motivation had a positive and significant effect toward the employee’sperformance;(5) discipline had a positive and significant effect toward the employee’s performance.